Logics to formalise p-adic valued probability and their applications. Issue 3 (4th May 2018) - Ilić Stepić, Angelina; Ognjanović, Zoran
Abstract: In this paper, we focus on the main results which we have developed to obtain different propositional logics for reasoning about p -adic valued probabilities. Each of these logics is a sound, complete, and decidable extension of classical propositional logic. Also, we show some applications of these logics in modelling cognitions.